International banking: its role in Florida's economy at the outset of the twenty-first century - Roussakis , Emmanuel N. (2001)
One of the most remarkable economic developments of the 1970s for the State of Florida was its emergence in the international financial world. Florida's economy, which until then was essentially relying on tourism, agriculture and the construction industry, began during the 1970s to gradually acquire a new dimension--international banking. Florida's proximity to Central and South American markets, its bilingual population, and the promulgation by the state of international banking legislation have all contributed to Miami's emergence--both nationally and internationally--as a specialized Latin American banking center.With international banking a major financial activity, its impact is felt throughout the Florida economy. Employment and office expenditures have a direct effect on local income. However, the total economic impact of international banking activities on the local economy is even more important when the multiplier effect of all direct and indirect expenditures associated with international banking is factored in. The purpose of this study is to describe the size and composition of international banking activities in Miami and to identify the effects of these activities for Miami-Dade County and, more broadly, for the Florida economy. To quantify this information a survey was undertaken in February 2000 among banking institutions in Miami-Dade. *  Although other financial institutions, such as security firms, provide international services, this survey was limited to commercial banks and Edge Act corporations.